Overexpression of MicroRNA-10a in Germ Cells Causes Male Infertility by Targeting Rad51 in Mouse and Human - Gao, Huihui; Wen, Hui; Cao, Congcong; Dong, Daqian; Yang, Chenhao; Xie, Shengsong; Zhang, Jin; Huang, Xunbin; Huang, Xingxu; Yuan, Shuiqiao; Dong, Wuzi (Frontiers in Physiology, 2019)
Spermatogenesis is a complicated process including spermatogonial stem cells (SSCs) self-renewal and differentiates into mature spermatozoa. MicroRNAs (miRNAs) as a class of small non-coding RNAs play a crucial role during the process of spermatogenesis. However, the function of a plenty of miRNAs on spermatogenesis and the potential mechanisms remain largely unknown. Here, we show that genetically conditional overexpressed miR-10a in germ cells caused complete male sterility, characterized by meiotic arrested in germ cells. Analysis of miR-10a overexpression mouse testes reveals that failure of double strand break (DSB) repairs and aberrant spermatogonial differentiation. Furthermore, we identified Rad51 as a key target of miR-10a in germ cell by bioinformatics prediction and luciferase assay, which may be responsible for the infertility of the miR-10a overexpressed mice and non-obstructive azoospermia (NOA) patients. Our data show that miR-10a dependent genetic regulation of meiotic process is crucial for male germ cell development and spermatogenesis in both mouse and human. These findings facilitate our understanding of the roles of miRNA-10a in spermatogenesis and can afford a basis for the diagnosis, therapy, and precaution of the male sterility.